The Role of Internet of Things (IoT) on Human Resources in Industry 4.0 - Ulfa, Oktafina Noor (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid advancement of technology has had a significant impact on various sectors. Human resources are now required to develop technical and data-driven skills to support the adoption of technologies that connect devices for real-time data sharing, playing a crucial role in enhancing the efficiency and effectiveness of organizational operations. This research aims to analyze the role of the Internet of Things (IoT) on human resources in the Fourth Industrial Revolution (Industry 4.0). The research method employed is a literature review, gathering data from various academic sources such as journals, articles, books, and other relevant materials. The findings of this study indicate that the implementation of IoT can improve operational efficiency through real-time monitoring. Overall, IoT holds great potential for optimizing human resource management in the era of Industry 4.0; however, organizations must carefully manage the associated impacts.